Rom, Italien. Bauforschung am sog. Tempel A, Largo Argentina. Arbeiten und Ergebnisse der Jahre 2018 und 2019 (nach Vorarbeiten 2014, 2016 und 2017) - Zink, Stephan; Pflug, Jens (e-Forschungsberichte des DAI, 2019)
In 2018, the division of building archaeology (Architekturreferat) of the DAI head office in Berlin began investigating the architectural remains of the socalled Temple A at Largo Argentina. It is one of four temples at a site, which, as it seems, was first developed during the Mid Republican period (3rd cent. BCE) and existed throughout Roman Antiquity. Temple A is of particular interest for its architectural longue durée – it was transformed into a church during the early Medieval period. Therefore, the site of Temple A shows over 2200 years of cultic activity. The goal of this project is a close documentation of the site’s architectural remains and a new reconstruction of its phases of development and aesthetic transformations under ever- changing social, political, and environmental conditions.